Interrelationship among landscape, floristic-structural organization and demography of the tree component in araucaria forest Inter-relação entre paisagem, organização florístico-estrutural edemografia do componente arbóreo em floresta com araucárias - Cruz A.P.* (2018)
© 2018, Universidade Federal de Santa Maria. All rights reserved.The aim of this study was to investigate the interactions among the landscape spatial configuration, the floristic-structural organization and demographic rates of the tree component of a system of araucaria forest fragments, in Lages, Santa Catarina state. To do so, we developed a conceptual model of inter-relationship that was evaluated by Structural Equation Modeling. In 2010, the landscape metrics (area, distance from the nearest neighbor and edge-core ratio) and first vegetation inventory data were obtained. Permanent plots were allocated in five forest fragments and forest corridor, where all tree individuals with cbh (circumference at breast height, measured at 1.30 ground) greater than or equal to 15.7 cm were identified and measured. In 2014, the second inventory was conducted, with the inclusion of recruits and counting dead and survivor’s individuals, followed by the determination of demographic rates. The data were analyzed through Principal Component Analysis (PCA), Principal Coordinates Analysis (PCoA), Structural Equation Modelling, and Generalized Linear Models (GLM). The results showed that the landscape structure (PCA 1) had a significant influence only on the floristic-structural organization of the tree component, indicated by the preferential distribution of tree species in response to fragmentation intensity. In turn, the demographic rates (basal area gain and loss rates, and mortality rate) were influenced by structural aspects of vegetation (abundance and basal area). We conclude that there was floristic-structural variation associated to the spatial configuration of fragments in the landscape and that the demographics rates presented relation with forest successional stage, synthetized by structural variables of basal area and abundance.